2007
DOI: 10.1038/sj.onc.1210266
|View full text |Cite
|
Sign up to set email alerts
|

Riboregulator H19 induction of MDR1-associated drug resistance in human hepatocellular carcinoma cells

Abstract: Acquisition of drug resistance is one of the main obstacles encountered in cancer chemotherapy. Overexpression of multi-drug resistance 1 (MDR1) gene and its protein product P-glycoprotein, accompanied with a decrease in doxorubicin accumulation level, was observed in doxorubicin-resistant R-HepG2 cells, a subline derived by selection of human hepatocellular carcinoma HepG2 cells with doxorubicin. In addition, Northern-blot analysis revealed an eight fold upregulation of the imprinted H19 mRNA in R-HepG2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 12 publications
2
131
1
Order By: Relevance
“…31,32 However, other reports have demonstrated that chemotherapeutic drugs may induce specific epigenetic modifications (hypomethylation) at the MDR1 locus and may up-regulate MDR1 by transcriptional activation. 33,34 In the current study, there was a significant correlation between MDR1 methylation and negative Pgp expression. Our results support the conclusion that methylation of the MDR1 promoter negatively regulates Pgp protein expression in BAC.…”
Section: Discussionmentioning
confidence: 83%
“…31,32 However, other reports have demonstrated that chemotherapeutic drugs may induce specific epigenetic modifications (hypomethylation) at the MDR1 locus and may up-regulate MDR1 by transcriptional activation. 33,34 In the current study, there was a significant correlation between MDR1 methylation and negative Pgp expression. Our results support the conclusion that methylation of the MDR1 promoter negatively regulates Pgp protein expression in BAC.…”
Section: Discussionmentioning
confidence: 83%
“…4B). Drug resistance in tumor cells, including HCC cells, is also associated with the expression of the multidrug resistance 1 (MDR1) gene (18). Moreover, repetitive treatment with doxorubicin is known to enhance multidrug resistance of cancer cells (19).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms involved in WT1 regulation of MDR1 expression in HCC cells are not fully understood at the moment. These may include a direct interaction of WT1 with MDR1 promoter as described in leukemia cells (43), or could involve indirect mechanisms such as the expression of H19, an inducer of MDR1 transcription in liver cancer cells (18) identified in our microarray experiments as a WT1-dependent gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, results show that the level of H19 RNA is elevated in the multidrug resistance variant of HCC cell lines. Here doxorubicin resistance phenotype is related to H19 over-expression (Tsang et al, 2007). H19 provides a novel and clinically useful diagnostic marker for prognosticating human bladder carcinoma.…”
Section: H19 Is Induced By Hypoxia -The P53 Brakes and The Hif-1α Enginementioning
confidence: 99%